Improving the Usability of the Sumber Alam Express Ticket Booking Application using the Heuristic Evaluation Method - Kurniawan, Rizki Candra; Frobenius, Arvin Claudy (Sistemasi: Jurnal Sistem Informasi, 2025)
This study aims to evaluate improvements in the usability quality of the Sumber Alam Express application prototype using the Heuristic Evaluation method. The test results show that out of the ten heuristic evaluation factors, nine received high/agree ratings, while one factor received a moderate/neutral rating. There was a significant improvement across all factors compared to the previous study. Notably, "help users recognize, diagnose, and recover from errors" increased by 43.7%, and "help and documentation" improved by 42.5%. The only factor that remained at a neutral level was "flexibility and efficiency of use," which was due to the absence of shortcut features in the prototype—despite the application's flow remaining clear and easy to understand. The validity test indicated that one questionnaire item was invalid, mainly due to the limited number of respondents. This study involved 10 purposively selected respondents with diverse backgrounds, including employees and students who are active users, users of similar applications, and a frontend developer. Although the number of respondents was smaller than in the previous study, the diversity and depth of their experience ensured a comparable level of data representativeness. This research acknowledges its limitations, particularly the small sample size and partial instrument validity, both of which were constrained by time and resource limitations during the data collection process.